(untitled) (Research, Society and Development, 2022)
During dental appointments, patients often present anxiety and exacerbated fear, especially in surgical procedures. These reactions can promote systemic alterations, such as elevated blood pressure, fainting, and convulsions. The aim of this study was to evaluate the level of anxiety of patients during the lower third molar extraction procedure, seeking indicative parameters of possible complications and, at the same time, contributing to a safe and less uncomfortable procedure for the patient. Forty patients needing extraction of the lower third molar were selected. The study had an evaluator to monitor the systemic variables: blood pressure, oxygen saturation, respiratory and heart rate - while the same surgeon performed the surgical procedures, always using the same surgical technique for all patients. At the anamnesis and at the end of the surgery, the patients answered a visual analogue scale (VAS) questionnaire on anxiety. The results showed that for the four variables observed during the surgery, only the oxygen saturation did not present a statistically significant variation during the procedure. All the others showed changes, mainly during the use of the high-speed engine. We concluded that anxiety, fear and stress showed influences on systemic factors during the extraction procedure. It shows the importance of careful anamnesis and the knowledge of patient systemic diseases before starting any surgery to prevent risks or complications.